Myocardial tissue characterization using cardiac magnetic resonance in patients with acute hypertensive crisis, raised cardiac troponin and normal or unobstructed epicardial coronary arteries - Talle, Mohammed Abdullahi (Stellenbosch : Stellenbosch University, 2023)
Talle, Mohammed Abdullahi. 2023. Myocardial tissue characterization using cardiac magnetic resonance in patients with acute hypertensive crisis, raised cardiac troponin and normal or unobstructed epicardial coronary arteries. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available at: https://scholar.sun.ac.za/items/a4a35df7-78bb-4527-ace6-9bbbe0f6fb48